Analyzing the aggressive behavior of domestic violence perpetrators - Andriani, Wiwin; Afdal, Afdal (Universitas Negeri Padang, 2020)
The study was conducted by analyzing the aggressive behavior of domestic violence perpetrators which can be seen through how much the contribution of aggressive behavior between sub-variables. This research method uses a quantitative approach with descriptive methods. The subjects in this study were perpetrators who lived in the city of Padang and were taken using purposive sampling techniques, amounting to 82 people. Data is collected through the Aggressive Behavior Inventory Instrument for Domestic Violence developed from Buss theory about aspects of aggressive behavior that contains 4 sub, including physical aggression (4 items), verbal aggression (7 items), anger (3 items) and hostility (2 items). The instrument uses a Likert scale model that has five alternative answers with interval data and analyzed with descriptive statistical techniques and simple linear regression analysis. The research findings show that on average the figure of aggressive domestic violence perpetrators is in the moderate category by 71% and aggressive behavior in terms of verbal aggression contributes to physical aggression of 10.3% while aggressive behavior itself contributes to verbal aggression by 65.8%. With the results of this study become input for therapists/counselors sone of them is through family counseling with an experimental approach that prioritizes now and here experience.